THE COTTON INDUSTRY IN UZBEKISTAN DURING THE SECOND WORLD WAR (International Congress on Economics, Management and Business Studies, 2026)
This article analyses, on the basis of historical sources, the activities of the cotton industry of Uzbekistan during the Second World War, its strategic significance for the rear-area economy, and its contribution to the military defense system. The article examines how the sector was developed under the severe conditions of wartime — amid shortages of labor and machinery, problems with irrigation systems, and changes in agriculture. It argues that the infrastructural and economic foundation created by the cotton industry during the war years served as an important basis for the restoration of the republic's national economy in the post-war period.
Keywords: Second World War, Uzbekistan agriculture, cotton industry, home front, national economy, strategic raw materials, economic recovery.